Severe dental fluorosis in juvenile deer linked to a recent volcanic eruption in Patagonia - Fluck, Werner Thomas (2013)
The Puyehue-Cordon Caulle volcanic eruption deposited large amounts of tephra (ashes) in over 7.5 million ha of Argentina in June of 2011. Tephra were considered chemically innoxious based on water leachates, surface water fluoride levels determined to be safe, and livestock losses attributable to inanition and excessive tooth wear. To evaluate effects on wild ungulates, we sampled wild red deer (Cervus elaphus) at 100 km from the volcanic eruption in Sept-Oct 2012. Here we show that these tephra caused severe dental fluorosis, with bone fluoride levels reaching up to 3720 ppm. Among subadults, tephra caused pathological development of newly emerging teeth typical of fluorosis, including enamel hypoplasia, breakages, pitting, mottling, and extremely rapid ablation of entire crowns down to underlying pulp cavities. The loss of teeth functionality affected physical condition and none of the subadults were able to conceive. Susceptibility to fluorosis among these herbivores likely resides in ruminant food processing: a) mastication and tephra size reduction, b) thorough and repeated mixing with alkaline saliva, c) water-soluble extraction in the rumen, and d) extraction in the acidic abomasum. Although initial analyses of water and tephra was interpreted not to present a concern, ruminants as a major component of this ecosystem are shown to be highly susceptible to fluorosis, with average bone level increasing over 36-fold during the first 15.5 months of exposure to tephra. This is the first report of fluorosis in wild ungulates from volcanic eruptions. The described impact will reverberate through several aspects of the ecology of the deer, including effects on population dynamics, morbidity, predation susceptibility, as well as other components of the ecosystem like the scavenger and plant communities. We also anticipate further impact on livestock production systems, yet as of now, existence of fluorosis has not been recognized.